Pipeline walking and anchoring considerations in the presence of riser motion and inclined seabed - Reda, A.; Sultan, I.; Howard, Ian; Forbes, G.; McKee, Kristoffer (Elsevier, 2018)
Steel Catenary Risers (SCRs), are increasingly becoming an attractive option for many deepwater field developments. SCRs are typically used to transport fluids between floating production vessels and pipelines. Typical uses may also involve the transport of produced fluids from a subsea production system to a floating production vessel or the transport of gas or water for re-injection into the producing reservoirs. The floating production vessel on which the steel catenary riser is supported will be subject to motions caused by environmental loads, and influenced by the mooring system and other risers. Horizontal movement of the vessel causes changes in the riser catenary configuration in near, mean, and far positions. On the seabed, the riser is connected to a pipeline that extends for some distance from the riser touchdown point, to its tie-in point on a pipeline or other facility. Effective tension at the touchdown point is necessary to maintain the riser configuration which may cause the pipeline to walk in the axial direction. The development of axial walking is in part due to the pull experienced on the pipeline at the touchdown point from the SCR tension. In this paper, the results of the effective axial force and the pipeline end expansion using a finite element study are presented to highlight the effect that the changing SCR tension, combined with the thermal transients and a global seabed slope along the pipeline length, has on the pipeline walking. Additionally, the paper provides some guidance in regards to the selection of the optimum location for the hold-back anchors, to ensure that pipeline walking does not compromise the integrity of both the SCR and the pipeline system. In general, the results show that SCR bottom tension provides the dominant walking mechanism and can exceed the other walking mechanisms associated with thermal transients and seabed slope. For a straight short pipeline, in the range of 2–3 km, where there is no lateral buckling, it is recommended to install the anchor towards the PLET (Pipeline End Termination) and away from the SCR transition point.